HTR1D regulates the PI3K/Akt signaling pathway to impact hepatocellular carcinoma development and resistance to sorafenib - Yingai Zhang; Yuting Zhang; Shuai Zhou; Mujeeb Ur Rehman; Fankai Lin; Jianquan Zhang; Hailong Zhou (BMC Cancer)
Abstract Background Hepatocellular carcinoma (HCC) has a poor prognosis, partly due to resistance to treatments like sorafenib. The 5-hydroxytryptamine receptor 1D (HTR1D) is involved in cancer progression through the PI3K/Akt pathway, but its role in HCC is not well understood. This study investigates HTR1D’s expression, function, and potential as a prognostic marker in HCC. Methods First, the correlation between HTR1D and hepatocellular carcinoma was analyzed using the TCGA database, and the expression level of HTR1D in clinical samples was detected by qPCR. Then the siRNA was transfected into Huh-7 and Hep3B cells, and the cell proliferation ability, colony formation ability, migration and invasion ability were detected with or without sorafenib. And the expression of the PI3K/Akt pathway was detected by Western Blot. Finally, the potential of HTR1D as a predictive marker for patient prognosis was evaluated by immunohistochemistry. Results Analysis of TCGA data showed that methylation of the HTR1D gene was associated with cancer status. Clinical samples confirmed significant differences in HTR1D expression between HCC and adjacent tissues, with higher expression correlating with poorer patient prognosis. Interference with HTR1D gene expression demonstrated its role in promoting HCC proliferation, migration, and drug resistance through the PI3K/Akt pathway. These findings were validated in a mouse model. Immunohistochemical analysis of clinicopathological samples suggested that HTR1D could be a valuable prognostic marker for HCC. Conclusion HTR1D is highly expressed in hepatocellular carcinoma tissues, and it can influence hepatocellular carcinoma development and resistance to sorafenib by regulating the PI3K/Akt signaling pathway. In addition, HTR1D has potential as a prognostic indicator.